Digital vs. Traditional Remittance Preferences among Overseas Filipino Workers: Patterns, Barriers, and Behavioral Drivers - Rojas, Enrico D.; Narsico, Peter G. (Future Science / FSH-PH Publications, 2025)
This study examines the remittance method preferences of Overseas Filipino Workers (OFWs) amid growing digitalization in financial services. It explores usage patterns, country-level differences, and factors influencing the adoption of digital versus traditional remittance channels. Employing a descriptive-comparative design, the study analyzed responses from 400 OFWs across five global regions, gathered through online surveys and community networks. Chi-square tests of independence assessed associations between remittance preferences, countries of employment, and regional groupings. Results revealed significant differences across countries. OFWs in the United States and the United Arab Emirates exhibited high digital adoption (65.2% and 69.8%, respectively), citing convenience and cost-efficiency as key motivators. Conversely, OFWs in Taiwan, Hong Kong, and Singapore preferred traditional remittance centers due to trust and technological limitations. A significant association was found between country and remittance method, χ²(17, N = 400) = 78.24, p < .001, while regional differences between Asia and North America were not statistically significant, χ²(1, N = 337) = 1.33, p = .25. These findings underscore the need for user-centered financial technologies that are both inclusive and responsive to OFWs’ diverse socioeconomic contexts and digital competencies.